Literature review of modification of u-type savonius wind turbine rotor for low wind speeds - Alfatih, Muhammad Danang Ilham; Adiwibowo, Priyo Heru; Saptono, Renaldi Prima; Fani, Rayhan Aulia Iman; Pambudi, Dimas Ridho; Ciptafarizi, Muhammad Zardana; Setiawan, Kharis (JMEL : Journal of Mechanical Engineering Learning, 2024)
A wind turbine is one of the tools that can be used to convert wind energy into electrical energy. The increasing need for electrical energy in Indonesia and fossil fuels are running low, so alternative to fossil fuels are needed. One of them is a wind turbine that can convert wind energy into wind mechanical energy into kinetic energy in the form of turbine blades that are used to rotate generators that can produce electricity. Indonesia is an area that has low wind speed. This study aims to analyze the effect of U-type savonius wind turbine rotor modification at low wind speeds. The research method used is a qualitative method in which we conduct library research on various literature to examine the effect of turbine rotor modification. The results obtained are the addition of a guide vane or deflector and the increase in the number of blades on the turbine rotor can improve the performance of the U-type savonius wind turbine.